Multicultural Competence of Elementary Teacher Education Students - Fatmawati, Laila; Prama Dewi, Kirana; Wuryandani, Wuri (International Journal of Elementary Education, 2023)
Multicultural competence is essential for a country that has diversity, such as Indonesia. At the individual level, multicultural competence helps students appear successful in modern society and achieve personal development to a complete or collective level. People with high multicultural competence can work together to reduce intercultural conflict and build prosperity for all humanity. As elementary teacher candidates, elementary teacher education students are expected to have high multicultural competence. This study aimed to measure the multicultural competence of primary teacher education students. The research method used was a survey by a questionnaire distributed to teacher education students. The data analysis technique used is descriptive statistics. The survey results show that 85 students have very high multicultural competence, 34 students have high multicultural competence, one has medium multicultural competence, and one is very low. Cultural Awareness Competence is 24.57%; understanding of own and others' cultures indicator is 22.52%; Cultural Competence indicator is 24.89%. The Cultural Encounter indicator is 28.02%. It was concluded that elementary teacher education students already have high multicultural competence.